Nano VS₄ in-situ grown in three-dimensional honeycomb macroporous carbon enabling high-rate and long-life lithium storage - Yuan, Yongfeng (2023)
Poor Li+ diffusion kinetics and severe structure deterioration limit application of VS4 in lithium-ion batteries. Herein, three-dimensional honeycomb macroporous carbon is synthesized by polyvinylpyrrolidone, using compactly stacked SiO2 microsphere as the sacrificial template. Then, VS4 nanoparticles and nanoflakes are in-situ grown in the macropores of three-dimensional honeycomb carbon by solvothermal reaction. Nano VS4 is anchored to polyvinylpyrrolidone-derived amorphous carbon by strong chemical bonds. The composite exhibits extraordinary rate capability (533 mAh g−1 at 5 A g−1), high reversible capacity (1150 mAh g−1 at 0.2 A g−1), and stable long-term cycling performance (1253 mAh g−1 after 200 cycles at 0.2 A g−1, 960 mAh g−1 after 500 cycles at 1 A g−1, 201 mAh g−1 after 3500 cycles at 5 A g−1). The specific capacity of the composite includes VS4 and carbon. The intercalation reaction of VS4 contributes to the major capacity. The kinetics properties are significantly improved, including the dominant capacitive behavior, high diffusion coefficients of Li ions, low reaction impedance. Outstanding lithium storage performance is ascribed to well-dispersed nano VS4 in the highly conductive honeycomb carbon macropores and the intimately coupling between them by chemical bonds that ensure the excellent structure stability and fast electron/ion transfer of VS4.